1991
DOI: 10.1080/03601239109372753
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of atrazine and alachlor in soil amended with sludge, manure and activated carbon

Abstract: Greenhouse studies were conducted to determine the influence of waste-activated carbon (WAC), digested municipal sewage sludge (DMS), and animal manure on herbicidal activity of atrazine [2-chloro-4-(ethylamino)-6-(isopropylamino)-s-trazine] and alachlor [2-chloro-2',6'-diethyl-N-(methoxymethyl)acetanilide] in a Plainfield sandy soil. Amendments generally reduced bioactivity against oat (Avena sativa L.) and Japanese millet (E. crus-galli frumentacea).The extent to which herbicide phytotoxicity was inhibited d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Guo et al (1991) suggested that atrazine and alachlor degradation could be inhibited by the presence of waste activated carbon, and stimulated by other uncharred amendments, such as municipal sewage sludge and manure. An increase on atrazine degradation by the addition of organic amendments to a sandy loam soil was also reported by Mukherjee (2009).…”
Section: Effect Of Carbonaceous Materials On Pesticide Degradationmentioning
confidence: 99%
“…Guo et al (1991) suggested that atrazine and alachlor degradation could be inhibited by the presence of waste activated carbon, and stimulated by other uncharred amendments, such as municipal sewage sludge and manure. An increase on atrazine degradation by the addition of organic amendments to a sandy loam soil was also reported by Mukherjee (2009).…”
Section: Effect Of Carbonaceous Materials On Pesticide Degradationmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the effects of various environmental factors on the growth ability of the tested microorganisms (Pattanasupong et al, 2004). On the other hand, it was found that various materials were used as soil amendments, nutrients, to increase and enhance the degradation potential of xenobiotics such as Yard manure compost (Guo et al, 1991;Cole et al, 1995;Gan et al, 1996;Zheng and Cooper, 1996;Vogel, 1996;Grigg et al, 1997;Leoni et al, 1997), biogas slurry and compost (Kadian et al, 2008;Belal et al, 2008). However, after remediation toxicity assessments are needed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, at such high concentrations, an overload of the GAC and PAC (Table 2) ]) largely consists of results of pesticide uptake by plants from polluted soils. The plants studied by Guo et al (1991) were oat and Japanese millet, and the investigated herbicides atrazine and alachlor. Successful reductions of pesticide uptake was only achieved when adding high concentrations (43.8%) of waste AC (WAC).…”
Section: Reduction Endpoints In Soilsmentioning
confidence: 99%
“…Therefore, researchers started to use alternative carbon material like e.g. biochar (Yu et al, 2009), coke breeze (Zimmerman et al, 2004;Millward et al, 2005), waste AC (Guo et al, 1991), fly ash (Burgess et al, 2009), and many more. Further drawbacks and side effects of AC amendment, such as the stability of the AC material, physical alteration of the matrices, direct or indirect harmful effects on, and nutrient availability to organisms will be discussed in "Factors potentially reducing the efficiency of AC amendment and other side effects" section.…”
Section: Introductionmentioning
confidence: 99%